PERSEPSI GURU TENTANG KOMPETENSI PROFESIONAL KEPALA SEKOLAH MENENGAH ATAS NEGERI (SMAN) KOTA PADANG - Andreki Ariesta; Anisah Anisah; Sulastri Sulastri; Tia Ayu Ningrum (STKIP Subang, 2026)
This study is motivated by the importance of a school principal's professional competence in enhancing the quality of instruction and the effectiveness of school management. According to the Regulation of the Minister of Education and Culture (Permendikdasmen) Number 21 of 2025, professional competence is a crucial attribute that every principal must possess to advance their school. This quantitative descriptive study aims to describe teachers' perceptions regarding the professional competence of principals at state senior high schools (SMA Negeri) in Padang City. The study population consisted of 1,024 teachers from 17 state senior high schools. A sample of 157 teachers was selected using multistage stratified random sampling a combination of cluster sampling and proportional random sampling. Data were collected using a validated and reliable 30-item questionnaire based on a 5-point Likert scale, covering six indicators: curriculum development, student-centered learning, instructional supervision, fostering innovation, entrepreneurial values, and transformational leadership. The results indicate that the learning dimension received a score of 4.56 (competent) and the school development dimension received a score of 4.52 (competent), resulting in an overall average score of 4.54 (competent). These findings suggest that, in general, principals have effectively demonstrated their professional competence, although areas such as curriculum evaluation, literacy strengthening, and collaborative supervision require further reinforcement.